Capturing the Essence of Contemporary Law School Engagement: Tech, Social Justice and Online Engagement - Maxine Evers; Genevieve Wilkinson (Legal Education Review)
Amidst an emerging focus on technology in the curriculum and a sustained student commitment to social justice, the global COVID-19 pandemic drastically and permanently changed the tertiary learning environment. Law students and educators rapidly moved to online learning, resulting in many challenges, including isolation and disengagement for some students. Co-curricular on-campus programs were also impacted with many optional activities paused while educators grappled with the design and delivery of teaching in the online environment. Using a case study analysis, this article discusses how a co-curricular program that blends technology and social justice thrived during the COVID-19 pandemic, enabling students to continue to engage in volunteer opportunities, nurture a sense of wellbeing and develop their resilience as learners and law students. Theories of student engagement are analysed with two main objectives: to identify the key lessons from this challenging period applicable to co-curricular programs; and to assess the impact of online delivery on situated learning experiences. This article contributes to the literature exploring student engagement and the purpose of legal education beyond the curriculum. Drawing on measurable outcomes and observations, we conclude that our response to the challenges of the COVID-19 pandemic has taught us key valuable and sustainable lessons in situated learning and student wellbeing that we can apply as we settle into a hybrid learning environment.